If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 + 8b = 4(5b + -5) Reorder the terms: 16 + 8b = 4(-5 + 5b) 16 + 8b = (-5 * 4 + 5b * 4) 16 + 8b = (-20 + 20b) Solving 16 + 8b = -20 + 20b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-20b' to each side of the equation. 16 + 8b + -20b = -20 + 20b + -20b Combine like terms: 8b + -20b = -12b 16 + -12b = -20 + 20b + -20b Combine like terms: 20b + -20b = 0 16 + -12b = -20 + 0 16 + -12b = -20 Add '-16' to each side of the equation. 16 + -16 + -12b = -20 + -16 Combine like terms: 16 + -16 = 0 0 + -12b = -20 + -16 -12b = -20 + -16 Combine like terms: -20 + -16 = -36 -12b = -36 Divide each side by '-12'. b = 3 Simplifying b = 3
| (x(-7+i))(x(-7-i))(x+2)=y | | n/9-4=4 | | 6xy+8xy= | | (4x+3)-(9x+5)=0 | | 4x^2+13x-16=2-8x | | (x(-7+i))(x(-7-i))(x+2)=0 | | 39.2=p*112 | | 6n+18=(-2n)+2 | | 8-37a-15a^2=0 | | 14=y+13 | | -5.4=1 | | 2-6d=14 | | .11-x=.29 | | -4p^2-6p+15=0 | | n=-1.8 | | 2(x-1)-3x=-2 | | 4=-8y+1 | | (5x+3y)(3m+6w)= | | 4(x-9)=x+3(x-12) | | 5m^2-3m+3=2 | | 5=-3+2u | | 2=-4(g-2) | | 4(x-9)=x | | 10(n+2)=2 | | 3(x+4)-4(x-5)=63 | | 9(x+5)=2x+4x-15 | | 2x-(3+2x)+6= | | -27-4x=7(x+4) | | 4x-3(-6+x)=21 | | a^2+4a=25 | | 7(p-8)= | | (-15)-(6)= |